Conductive paste, high thermal conductivity material and semiconductor device

A conductive paste with reduced silver content, using a thermosetting resin and alumina particles, addresses the environmental and cost issues of silver-based pastes by maintaining conductivity and improving dispersibility and contact between particles, suitable for semiconductor devices.

JP2025005956APending Publication Date: 2025-01-17SUMITOMO BAKELITE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023106432
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Conductive pastes containing silver emit a large amount of carbon dioxide during manufacturing due to the high environmental impact of silver, leading to high material costs and a need for materials with reduced silver content while maintaining good conductivity.

Method used

A conductive paste comprising a thermosetting resin, silver particles, and alumina particles, with specific mass content ratios and viscosity ranges, to improve dispersibility and contact between particles, reducing silver content while maintaining conductivity.

Benefits of technology

The conductive paste achieves reduced silver content with good conductivity, improved dispersibility, and enhanced thermal and electrical conductivity, suitable for semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005956000001_ABST
    Figure 2025005956000001_ABST
Patent Text Reader

Abstract

To provide conductive pastes with reduced silver content while having good conductivity.SOLUTION: A conductive paste contains thermosetting resin (A), silver particles (b1), and alumina particles (b2), the content of silver particles (b1) is between 20 mass% and 65 mass% when the total amount of the conductive paste is 100 mass%, and the viscosity of the conductive paste is between 0.1 Pa s and 150 Pa s, as measured with a BF-type viscometer at a temperature of 25°C and a rotation speed of 5 rpm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a conductive paste, a highly thermally conductive material, and a semiconductor device. [Background technology]

[0002] A semiconductor device has a structure in which, for example, a semiconductor element is stacked on a substrate, and electrodes of the semiconductor element are connected to electrodes on the substrate. In such a semiconductor device, a paste-like resin composition is used to bond a semiconductor element onto a substrate, that is, the semiconductor element is laminated on the substrate via an adhesive layer formed from a paste, for example.

[0003] Pastes used for bonding semiconductor elements are required to have, for example, electrical conductivity and thermal conductivity, and metal particles are blended in as components that impart these properties.

[0004] For example, Patent Document 1 describes a thermosetting resin composition containing (A) plate-shaped silver microparticles, (B) silver powder, and (C) a thermosetting resin, in which 1 to 20 parts by mass of component (C) is blended when the total amount of the silver microparticles of component (A) and the silver powder of component (B) is taken as 100 parts by mass, with the aim of providing a thermosetting resin composition for semiconductor bonding and a thermosetting resin composition for light-emitting devices that have high thermal conductivity and excellent heat dissipation properties and can satisfactorily bond semiconductor elements and light-emitting elements to a substrate. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2014-194013 A Summary of the Invention [Problem to be solved by the invention]

[0006] In recent years, there has been an increasing demand for materials that have a low environmental impact and emit less carbon dioxide during the manufacturing process, and there is also a demand for conductive pastes that emit less carbon dioxide during the manufacturing process.

[0007] On the other hand, conductive pastes containing silver have excellent conductivity, but the use of silver, which has a large environmental impact, results in a large amount of carbon dioxide emissions during the manufacturing process. In addition, the use of silver, a precious metal, results in high material costs. Therefore, there is a demand for conductive pastes with a reduced silver content while still maintaining good conductivity.

[0008] The present invention has been made in consideration of the above circumstances, and provides a conductive paste having good electrical conductivity and a reduced silver content. [Means for solving the problem]

[0009] According to the present invention, there are provided a conductive paste, a highly thermally conductive material, and a semiconductor device as described below. [1] A conductive paste comprising a thermosetting resin (A), silver particles (b1), and alumina particles (b2), the content of the silver particles (b1) is 20% by mass or more and 65% by mass or less, when the total amount of the conductive paste is 100% by mass, The conductive paste has a viscosity of 0.1 Pa·s or more and 150 Pa·s or less, as measured using a BF type viscometer at a temperature of 25°C and a rotation speed of 5 rpm. [2] The conductive paste according to [1], wherein a total content of the silver particles (b1) and the alumina particles (b2) is 40% by mass or more and 99% by mass or less, when the total amount of the conductive paste is 100% by mass. [3] The conductive paste according to [1] or [2], wherein the content of the thermosetting resin (A) is 1% by mass or more and 30% by mass or less, when the total amount of the conductive paste is 100% by mass. [4] The conductive paste according to any one of [1] to [3], wherein the thermosetting resin (A) includes one or more resins selected from the group consisting of an epoxy resin (a1) and a (meth)acrylic resin (a2). [5] The thermosetting resin (A) contains the epoxy resin (a1), The conductive paste according to [4], further comprising a (meth)acrylate compound. [6] The thermosetting resin (A) contains the (meth)acrylic resin (a2), The conductive paste according to [4], further comprising a (meth)acrylate compound and a low stress agent. [7] The silver particles (b1) have an average particle size D based on a volume-based particle size distribution measured by a flow particle image analyzer. 50 The flake silver particles have different The conductive paste according to any one of [1] to [6], wherein the alumina particles (b2) include spherical particles. [8] The flake silver particles have an average particle size D 50 Flake-shaped silver particles having an average particle size D of 0.1 μm or more and less than 6 μm 50 and flake-shaped silver particles having a size of 6 μm or more and 20 μm or less. [9] The average particle size D of the silver particles (b1) based on the volume-based particle size distribution measured by a flow particle image analyzer 50 (d1) and the average particle diameter D of the alumina particles (b2) 50 The conductive paste according to [7] or [8], wherein a ratio (d1 / d2) to (d2) is 1 or more and 4 or less.

[10] The conductive paste according to any one of [1] to [9], wherein a thixotropic index, which is a viscosity ratio (η0.5 / η5), is 0.1 or more and 20 or less, when the viscosity of the conductive paste measured using a BF type viscometer at a temperature of 25°C and a rotation speed of 0.5 rpm is η0.5 and the viscosity of the conductive paste measured at a temperature of 25°C and a rotation speed of 5 rpm is η5.

[11] The volume resistivity measured by the following method is 9.0×10 -2 The conductive paste according to any one of [1] to

[10] , having a resistivity of Ω·cm or less. (method) The conductive paste is applied onto a glass plate in a strip shape of 4 mm wide × 40 mm long × 0.05 mm thick. The conductive paste coating layer is then heated from 25°C to 175°C at a heating rate of 5°C / min in a nitrogen atmosphere with a residual oxygen concentration of less than 1000 ppm, and then heat-treated at 175°C for 60 minutes to form a hardened layer of the conductive paste. The resistance of the hardened layer of the conductive paste obtained is measured by a direct current four-electrode method using electrodes spaced 40 mm apart, and the volume resistivity is calculated.

[12] A highly thermally conductive material comprising a cured product of the conductive paste according to any one of [1] to

[11] .

[13] A substrate; A semiconductor element mounted on the base material via an adhesive layer, The adhesive layer comprises a cured product of the conductive paste according to any one of [1] to

[11] . Effect of the Invention

[0010] According to the present invention, it is possible to provide a conductive paste having good electrical conductivity and a reduced silver content. [Brief description of the drawings]

[0011] [Figure 1] 1 is a cross-sectional view illustrating an example of a semiconductor device according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the present invention will be described based on an embodiment.

[0013] In this embodiment, "A to B" indicating a numerical range means A or more and B or less, unless otherwise specified.

[0014] In the description of groups (atomic groups) in this embodiment, descriptions that do not indicate whether they are substituted or unsubstituted include both those that have no substituents and those that have a substituent. For example, an "alkyl group" includes not only an alkyl group that has no substituents (unsubstituted alkyl group) but also an alkyl group that has a substituent (substituted alkyl group).

[0015] In the present embodiment, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate."

[0016] <Conductive paste> The conductive paste of the present embodiment is a conductive paste containing a thermosetting resin (A), silver particles (b1), and alumina particles (b2), in which the content of silver particles (b1) is 20% by mass or more and 65% by mass or less when the total amount of the conductive paste is taken as 100% by mass, and the viscosity of the conductive paste, measured using a BF type viscometer at a temperature of 25°C and a rotation speed of 5 rpm, is 0.1 Pa s or more and 150 Pa s or less.

[0017] The conductive paste of the present embodiment can reduce the silver content while maintaining good conductivity.

[0018] The mechanism by which the conductive paste of this embodiment can reduce the silver content while maintaining good conductivity is not clear, but it is speculated that this is because the conductive paste contains thermosetting resin (A), silver particles (b1), and alumina particles (b2), the content of silver particles (b1) is within a certain range, and the viscosity of the conductive paste is within a certain range, which improves the dispersibility of the silver particles (b1) and alumina particles (b2) and improves the contact rate between the particles, thereby improving the conductivity of the conductive paste.

[0019] <Thermosetting resin (A)> The conductive paste of this embodiment contains a thermosetting resin (A). From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, the thermosetting resin (A) of this embodiment preferably contains one or more resins selected from the group consisting of polyester resins, epoxy resins, urethane resins, phenolic resins, melamine resins, vinyl resins, (meth)acrylic resins, and silicone resins, and more preferably contains one or more resins selected from the group consisting of epoxy resins and (meth)acrylic resins.

[0020] As the epoxy resin used as the thermosetting resin (A) of this embodiment, a general monomer, oligomer, or polymer having two or more glycidyl groups in one molecule can be used, and the molecular weight or molecular structure thereof is not particularly limited. From the viewpoint of improving the coating workability and adhesiveness of the obtained conductive paste, the epoxy resin of this embodiment may be, for example, a biphenyl type epoxy resin; a bisphenol type epoxy resin such as a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a tetramethyl bisphenol F type epoxy resin, a modified bisphenol A type epoxy resin, or a modified bisphenol F type epoxy resin; a stilbene type epoxy resin; a novolac type epoxy resin such as a phenol novolac type epoxy resin or a cresol novolac type epoxy resin; a multifunctional epoxy resin such as a triphenol methane type epoxy resin or an alkyl modified triphenol methane type epoxy resin; an aralkyl type epoxy resin such as a phenol aralkyl type epoxy resin having a phenylene skeleton or a phenol aralkyl type epoxy resin having a biphenylene skeleton; a naphthol type epoxy resin such as a dihydroxynaphthalene type epoxy resin or an epoxy resin obtained by glycidyl etherifying a dimer of dihydroxynaphthalene.

[0043] It is preferable that the epoxy resin contains one or more selected from the group consisting of epoxy resins; triazine nucleus-containing epoxy resins such as triglycidyl isocyanurate and monoallyl diglycidyl isocyanurate; phenol-type epoxy resins modified with bridged cyclic hydrocarbon compounds such as dicyclopentadiene-modified phenol-type epoxy resins; diglycidyl ethers of bisphenol compounds such as bisphenol A, bisphenol F, biphenol, etc. or derivatives thereof; diglycidyl ethers of diols having an alicyclic structure such as hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated biphenol, cyclohexanediol, cyclohexanedimethanol, cyclohexanediethanol, etc. or derivatives thereof; diglycidyl ethers of aliphatic diols such as butanediol, hexanediol, octanediol, nonanediol, decanediol, etc. or derivatives thereof; and triglycidyl ethers having a trihydroxyphenylmethane skeleton or an aminophenol skeleton.

[0021] Among these, from the viewpoint of improving the coating workability and adhesiveness of the obtained conductive paste, the epoxy resin of this embodiment more preferably contains one or more selected from the group consisting of bisphenol type epoxy resins and diglycidyl ethers of diols having an alicyclic structure, and further preferably contains one or more selected from the group consisting of bisphenol F type epoxy resins, modified bisphenol A type epoxy resins, and diglycidyl ethers of cyclohexanediol. Furthermore, from the viewpoint of more effectively improving the coating workability of the conductive paste, the epoxy resin of this embodiment preferably contains a liquid epoxy resin that is liquid at 25°C.

[0022] The (meth)acrylic resin used as the thermosetting resin (A) of this embodiment is, from the viewpoint of improving the storage stability of the obtained conductive paste, for example, a methyl (meth)acrylate type (meth)acrylic resin, an ethyl (meth)acrylate type (meth)acrylic resin, a propyl (meth)acrylate type (meth)acrylic resin, a butyl (meth)acrylate type (meth)acrylic resin, a 2-ethylhexyl (meth)acrylate type (meth)acrylic resin, a lauryl (meth)acrylate type (meth)acrylic resin, a stearyl (meth)acrylate type (meth)acrylic resin, a cyclohexyl (meth)acrylate type (meth)acrylic resin, a 2-hydroxyethyl (meth)acrylate type (meth)acrylic resin, a 2-propyl (meth)acrylate type (meth)acrylic resin, a 2-phenoxyethyl (meth)acrylate type (meth)acrylic resin, or a combination thereof.

[0113] It is preferable that the copolymer contains one or more resins selected from the group consisting of acrylic resin, chloro-2-hydroxyethyl (meth)acrylate type (meth)acrylic resin, ethylene glycol di(meth)acrylate type (meth)acrylic resin, diethylene glycol mono(meth)acrylate type (meth)acrylic resin, methoxyethyl (meth)acrylate type (meth)acrylic resin, glycidyl (meth)acrylate type (meth)acrylic resin, 1,4-cyclohexanedimethanol mono(meth)acrylate type (meth)acrylic resin, dicyclopentanyl (meth)acrylate type (meth)acrylic resin, dicyclopentenyl (meth)acrylate type (meth)acrylic resin, and isobornol (meth)acrylate type (meth)acrylic resin, and it is more preferable that the copolymer contains glycidyl (meth)acrylate type (meth)acrylic resin.

[0023] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the thermosetting resin (A) in the conductive paste of this embodiment is preferably 1 mass % or more, more preferably 2 mass % or more, even more preferably 3 mass % or more, and is preferably 30 mass % or less, more preferably 25 mass % or less, even more preferably 20 mass % or less, and even more preferably 17 mass % or less, when the total amount of the conductive paste is 100 mass %.

[0024] The conductive paste of this embodiment contains silver particles (b1) and alumina particles (b2) from the viewpoint of reducing the silver content while maintaining good conductivity. From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the total content of the silver particles (b1) and the alumina particles (b2) in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 40 mass% or more, more preferably 50 mass% or more, even more preferably 55 mass% or more, even more preferably 60 mass% or more, even more preferably 65 mass% or more, and is preferably 99 mass% or less, more preferably 95 mass% or less, even more preferably 90 mass% or less, and even more preferably 88 mass% or less.

[0025] <Silver particles (b1)> The conductive paste of this embodiment contains silver particles (b1). The shape of the silver particles (b1) of this embodiment is not particularly limited, and examples thereof include known shapes such as spherical, dendritic, string-like, flake-like, aggregated, and polyhedral shapes. In this embodiment, one or more types of silver particles having these shapes may be included, but from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the silver particles (b1) of this embodiment preferably contain flake-shaped silver particles.

[0026] The average particle size D of the silver particles (b1) of this embodiment is determined by a volume-based particle size distribution measured using a flow particle image analyzer. 50 is preferably 0.01 μm or more, more preferably 0.1 μm or more, even more preferably 0.5 μm or more, even more preferably 1 μm or more, and is preferably 30 μm or less, more preferably 20 μm or less, even more preferably 10 μm or less. Average particle size D 50 By setting the value of D at an appropriate value, it is easy to balance the thermal conductivity, sinterability, resistance to heat cycles, etc. 50 By setting the value to an appropriate value, it may be possible to improve the workability of applying / bonding the conductive paste. The particle size distribution of the silver particles (b1) (abscissa: particle diameter, ordinate: frequency) may be unimodal or multimodal.

[0027] The silver particles (b1) of this embodiment have an average particle size D 50 It is more preferable that the conductive paste contains two or more kinds of flake-shaped silver particles having different ions, and it is even more preferable that the conductive paste contains two kinds of flake-shaped silver particles. This makes it easier to adjust the viscosity of the conductive paste, and the balance between the spreadability and thixotropy can be adjusted, so that the particles can be further prevented from creeping up to the side or upper surface of the semiconductor element. Furthermore, since the contact rate between the silver-containing particles is further improved, a network is easily formed after sintering the conductive paste, and the thermal conductivity and electrical conductivity are further improved.

[0028] The silver particles (b1) of this embodiment have an average particle size D 50 When the composition contains two or more types of flake silver particles having different average particle diameters D 50 is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 2 μm or more, even more preferably 2.5 μm or more, even more preferably 3 μm or more, and is preferably less than 6 μm, more preferably 5 μm or less, even more preferably 4.5 μm or less, even more preferably 4 μm or less, even more preferably 3.5 μm or less; and 50 is preferably 6 μm or more, more preferably 6.5 μm or more, even more preferably 7 μm or more, even more preferably 7.5 μm or more, and is preferably 20 μm or less, more preferably 16 μm or less, even more preferably 13 μm or less, even more preferably 10 μm or less, even more preferably 9 μm or less, even more preferably 8.5 μm or less.

[0029] In addition, the silver particles (b1) of this embodiment have a particle size D 50 When the composition contains two or more different types of silver particles, the average particle size D of the silver particles (b1) is determined by the volume-based particle size distribution measured by a flow particle image analyzer. 50(d1) is preferably 0.1 μm or more, more preferably 1 μm or more, even more preferably 3 μm or more, even more preferably 4 μm or more, even more preferably 5 μm or more, even more preferably 5.5 μm, and is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, even more preferably 8 μm or less, even more preferably 7 μm or less, even more preferably 6 μm or less.

[0030] The average particle size D of the silver particles (b1) of this embodiment 50 can be obtained by measuring particle images using, for example, a flow particle image analyzer FPIA (registered trademark)-3000 manufactured by Sysmex Corp. More specifically, the particle size of silver particles (b1) can be determined by measuring the volume-based median diameter in a wet manner using this device.

[0031] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the content of silver particles (b1) in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 20 mass% or more, more preferably 23 mass% or more, even more preferably 26 mass% or more, even more preferably 28 mass% or more, even more preferably 30 mass% or more, and is preferably 65 mass% or less, more preferably 60 mass% or less, even more preferably 57 mass% or less, even more preferably 54 mass% or less, even more preferably 51 mass% or less, even more preferably 48 mass% or less, and even more preferably 46 mass% or less.

[0032] The silver particles (b1) of this embodiment may be surface-treated with one or more substances selected from the group consisting of carboxylic acids, saturated fatty acids having 4 to 30 carbon atoms, monovalent unsaturated fatty acids having 4 to 30 carbon atoms, long-chain alkylnitriles, and the like.

[0033] The silver particles (b1) of this embodiment are available from, for example, DOWA Hi-Tech Co., Ltd., Fukuda Metal Foil & Powder Co., Ltd., Tokuriki Honten Co., Ltd., and the like.

[0034] <Alumina particles (b2)> The conductive paste of this embodiment includes alumina particles (b2). The shape of the alumina particles (b2) of this embodiment is not particularly limited, and examples thereof include known shapes such as spherical, dendritic, string-like, flake-like, aggregated, and polyhedral shapes. In this embodiment, one or more types of alumina particles of these shapes may be included, but from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, it is preferable that the alumina particles (b2) of this embodiment include spherical alumina particles. In this embodiment, "spherical" is not limited to a perfect sphere, and also includes shapes with slight irregularities on the surface.

[0035] The average particle size D of the alumina particles (b2) of this embodiment 50 (d2) is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1 μm or more, even more preferably 1.5 μm or more, even more preferably 2 μm or more, even more preferably 2.5 μm or more, even more preferably 3 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, even more preferably 10 μm or less, even more preferably 7 μm or less, even more preferably 5 μm or less, even more preferably 4 μm or less, even more preferably 3.5 μm or less. The particle size distribution of the alumina particles (b2) (horizontal axis: particle diameter, vertical axis: frequency) may be either unimodal or multimodal.

[0036] Average particle size D of silver particles (b1) 50 (d1) and the average particle size D of alumina particles (b2) 50 The ratio (d1 / d2) to (d2) is preferably 1 or more, more preferably 1.2 or more, even more preferably 1.4 or more, even more preferably 1.6 or more, even more preferably 1.7 or more, even more preferably 1.8 or more, and is preferably 4 or less, more preferably 3 or less, even more preferably 2.5 or less, even more preferably 2.2 or less, even more preferably 2 or less, even more preferably 1.9 or less. By setting d1 / d2 within the above range, it becomes easy to adjust the viscosity of the conductive paste, and the balance between the spreadability and thixotropy can be adjusted, so that the creeping up to the side or upper surface of the semiconductor element can be further suppressed. Furthermore, since the contact rate between the silver-containing particles is further improved, a network is easily formed after sintering the conductive paste, and the thermal conductivity and electrical conductivity are further improved.

[0037] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the content of the alumina particles (b2) in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 10 mass% or more, more preferably 15 mass% or more, even more preferably 20 mass% or more, even more preferably 23 mass% or more, and is preferably 65 mass% or less, more preferably 60 mass% or less, even more preferably 55 mass% or less, and even more preferably 50 mass% or less.

[0038] The alumina particles (b2) of this embodiment may have their surfaces treated with one or more substances selected from the group consisting of carboxylic acids, saturated fatty acids having 4 to 30 carbon atoms, monovalent unsaturated fatty acids having 4 to 30 carbon atoms, long-chain alkyl nitriles, and the like.

[0039] <Inorganic filler> The conductive paste of this embodiment may contain an inorganic filler as necessary. However, the inorganic filler does not include silver particles (b1) and alumina particles (b2). From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the inorganic filler of this embodiment preferably contains one or more selected from the group consisting of metal particles of copper, gold, nickel, tin, lead, zinc, bismuth, antimony, or alloys thereof; silica such as fused silica, crystalline silica, and amorphous silica; silicon dioxide; alumina; aluminum hydroxide; silicon nitride; and aluminum nitride, and more preferably contains silica.

[0040] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the content of the inorganic filler in the conductive paste of this embodiment is preferably 0 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, and even more preferably 1 mass% or more, when the total amount of the conductive paste is 100 mass%, and is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, even more preferably 3 mass% or less, and even more preferably 2 mass% or less.

[0041] <(Meth)acrylate compounds> The conductive paste of the present embodiment may contain a (meth)acrylate compound as a diluent, which allows the conductive paste of the present embodiment to have a viscosity suitable for achieving application to a substrate and filling into fine details.

[0042] From the viewpoints of reducing the silver content while maintaining good electrical conductivity in a conductive paste and improving the applicability to a substrate and the ability to fill fine areas, the (meth)acrylate compound of the present embodiment preferably contains one or more monomers selected from the group consisting of a monofunctional (meth)acrylic monomer having only one (meth)acrylic group and a polyfunctional (meth)acrylic monomer having two or more (meth)acrylic groups, and more preferably contains both a monofunctional (meth)acrylic monomer and a polyfunctional (meth)acrylic monomer.

[0043] In the (meth)acrylate compound of the present embodiment, from the viewpoint of reducing the silver content while having good conductivity in a conductive paste and improving the applicability to a substrate and the ability to fill in fine areas, as a monofunctional (meth)acrylic monomer, for example, 2-phenoxyethyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tridecyl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethyl Hexyl diethylene glycol (meth)acrylate, methoxy polyethylene glycol (meth)acrylate, methoxy dipropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy diethylene glycol (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, phenylphenol ethylene oxide modified (meth)acrylate, isobornyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate quaternized, glycidyl (meth)acrylate, neopentyl glycol (meth)acrylic acid benzoate, 1,It is preferable that the compound contains one or more selected from the group consisting of 4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalic acid, 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloyloxyethyl acid phosphate, and polyoxypropylene monomethacrylate. Among these, from the viewpoint of reducing the silver content while maintaining good electrical conductivity in the conductive paste and improving the applicability to the substrate and the filling ability in fine areas, it is more preferable that the (meth)acrylate compound of the present embodiment contains one or more compounds selected from the group consisting of 2-phenoxyethyl (meth)acrylate and polyoxypropylene monomethacrylate.

[0044] In addition, in the (meth)acrylate compound of the present embodiment, from the viewpoint of reducing the silver content while maintaining good electrical conductivity in a conductive paste and improving the applicability to a substrate and the ability to fill in fine areas, polyfunctional (meth)acrylic monomers such as ethylene glycol di(meth)acrylate, 1,6-hexanediol dimethacrylate, trimethylolpropane tri(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, hexane-1,6-diol bis(2-methyl(meth)acrylate), 4,4'-isopropylidenediphenol di(meth)acrylate, , 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 1,4-bis((meth)acryloyloxy)butane, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, N,N'-(1,2-dihydroxyethylene)bis(meth)acrylamide and 1,4-bis((meth)acryloyl)piperazine. Among these, from the viewpoint of reducing the silver content while having good conductivity in the conductive paste and improving the application property to the substrate and the filling property in the fine details, the (meth)acrylate compound of the present embodiment more preferably contains one or two or more selected from the group consisting of ethylene glycol di(meth)acrylate and 1,6-hexanediol dimethacrylate.

[0045] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the (meth)acrylate compound in the conductive paste of this embodiment is preferably 0.1 mass % or more, more preferably 1 mass % or more, even more preferably 2 mass % or more, even more preferably 3 mass % or more, even more preferably 4 mass % or more, and is preferably 40 mass % or less, more preferably 30 mass % or less, even more preferably 25 mass % or less, and even more preferably 20 mass % or less, when the total amount of the conductive paste is taken as 100 mass %.

[0046] <Low stress agent> The conductive paste of the present embodiment may contain a low stress agent. This can improve the low stress properties of the conductive paste. From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the low stress properties of the conductive paste, the low stress agent of the present embodiment preferably contains one or more selected from the group consisting of silicone compounds such as silicone oil and silicone rubber; polybutadiene compounds such as polybutadiene maleic anhydride adducts; allyl ester resins, etc., more preferably contains a polybutadiene compound, and even more preferably contains a polybutadiene maleic anhydride adduct.

[0047] From the viewpoint of reducing the silver content and improving low stress properties while maintaining good conductivity in the conductive paste, the content of the low stress agent in the conductive paste of this embodiment is preferably 0 mass% or more, more preferably 0.001 mass% or more, even more preferably 0.01 mass% or more, even more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, and is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, and even more preferably 3 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0048] <Hardening agent> The conductive paste of the present embodiment may contain a curing agent. This can improve the curing property of the conductive paste. From the viewpoint of reducing the silver content and improving the curing property while maintaining good conductivity in the conductive paste, the curing agent of the present embodiment preferably contains one or more selected from the group consisting of acid anhydrides and phenolic compounds, more preferably contains a phenolic compound, and further preferably contains one or more phenolic compounds selected from the group consisting of bisphenols such as bisphenol F, bisphenol A, bisphenol S, tetramethyl bisphenol A, tetramethyl bisphenol F, tetramethyl bisphenol S, dihydroxydiphenyl ether, dihydroxybenzophenone, tetramethyl biphenol, ethylidene bisphenol, methyl ethylidene bis(methylphenol), cyclohexylidene bisphenol, biphenol, and derivatives thereof, and further preferably contains bisphenol F.

[0049] From the viewpoint of reducing the silver content and improving curability while maintaining good conductivity in the conductive paste, the content of the curing agent in the conductive paste of this embodiment is preferably 0 mass % or more, more preferably 0.1 mass % or more, even more preferably 1 mass % or more, even more preferably 2 mass % or more, even more preferably 3 mass % or more, and is preferably 20 mass % or less, more preferably 10 mass % or less, even more preferably 7 mass % or less, and even more preferably 5 mass % or less, when the total amount of the conductive paste is 100 mass %.

[0050] <Coupling Agent> The conductive paste of the present embodiment may contain a coupling agent, which can improve the adhesion between the conductive paste and the substrate. The coupling agent of the present embodiment is, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, for example, vinyl silanes such as vinyltrimethoxysilane and vinyltriethoxysilane; epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane; styryl silanes such as p-styryltrimethoxysilane; methacryl silanes such as 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane; 3-(trimethoxysilyl)propyl methacrylate, 3- It is preferable to include one or more selected from the group consisting of acrylic silanes such as acryloxypropyltrimethoxysilane; amino silanes such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; isocyanurate silanes; alkyl silanes; ureido silanes such as 3-ureidopropyltrialkoxysilane; mercapto silanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate silanes such as 3-isocyanatepropyltriethoxysilane; and polysulfide silanes such as bis(3-(triethoxysilyl)propyl)tetrasulfide.Among these, from the viewpoints of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, it is more preferable that the coupling agent of the present embodiment contains one or more types selected from the group consisting of epoxy silanes and polysulfide-based silanes, and it is even more preferable that the coupling agent contains one or more types selected from the group consisting of 3-glycidoxypropylmethyldiethoxysilane, 3-methacryloxypropyltrimethoxysilane, and bis(3-(triethoxysilyl)propyl)tetrasulfide.

[0051] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, the content of the coupling agent in the conductive paste of this embodiment is preferably 0 mass% or more, more preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.25 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, and even more preferably 1 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0052] <Curing aid> The conductive paste of this embodiment may contain a curing aid. This can promote the reaction between the epoxy resin and the curing agent. From the viewpoint of further promoting the reaction between the epoxy resin and the curing agent, the curing aid of this embodiment preferably contains one or more selected from the group consisting of phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines such as dicyandiamide, 2-phenyl-4,5-dihydroxymethylimidazole, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine; tertiary amines and derivatives thereof; and nitrogen atom-containing compounds such as quaternary ammonium salts of the amidines or tertiary amines. It is more preferable to contain one or more selected from the group consisting of amidines, tertiary amines and derivatives thereof, and it is even more preferable to contain one or more selected from the group consisting of dicyandiamide derivatives and 2-phenyl-4,5-dihydroxymethylimidazole.

[0053] From the viewpoint of further promoting the reaction between the epoxy resin and the curing agent, the content of the curing aid in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 0 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.03 mass% or more, even more preferably 0.05 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, and even more preferably 1 mass% or less.

[0054] <Radical polymerization initiator> The conductive paste of the present embodiment may contain a radical polymerization initiator. This may, for example, prevent insufficient curing, allow the curing reaction to proceed sufficiently at a relatively low temperature, or further improve the adhesive strength. From the viewpoint of allowing the curing reaction to proceed sufficiently, the radical initiator of the present embodiment preferably contains one or more selected from the group consisting of peroxides and azo compounds, and more preferably contains a peroxide.

[0055] From the viewpoint of sufficiently progressing the curing reaction, the radical polymerization initiator of the present embodiment preferably contains, as the peroxide, an organic peroxide such as a diacyl peroxide, a dialkyl peroxide, or a peroxyketal, and examples of such organic peroxides include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane and 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane; hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide; di(2-t-butylperoxyisopropyl)benzene and dicumyl peroxide; peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate; and peroxyesters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-hexyl peroxybenzoate, t-butylperoxy 2-ethylhexanoate. Among these, from the viewpoint of sufficiently progressing the curing reaction, it is more preferable that the radical polymerization initiator of the present embodiment contains one or two types selected from the group consisting of 1,1-di(t-butylperoxy)cyclohexane and dicumyl peroxide.

[0056] From the viewpoint of allowing the curing reaction to proceed sufficiently, the content of the radical polymerization initiator in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 0.001 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.05 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, and even more preferably 1 mass% or less.

[0057] <Solvent> The conductive paste of the present embodiment may contain a solvent. This adjusts the fluidity of the obtained conductive paste, thereby improving the handling and workability. The solvent of the present embodiment is, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the handling and workability, for example, ethyl alcohol, propyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isosuccinic acid, ethyl methacrylate ... Alcohols such as tearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol or glycerin; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octanone, isophorone (3,5,5-trimethyl-2-cyclohexen-1-one) or diisobutyl ketone (2,6-dimethyl-4-heptanone); esters such as ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl hexanoate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane, tributyl phosphate, tricresyl phosphate or tripentyl phosphate;It is preferable to include one or more selected from the group consisting of tetrahydrofuran, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane ethers; ester ethers such as 2-(2butoxyethoxy)ethane acetate; ether alcohols such as 2-(2-methoxyethoxy)ethanol; hydrocarbons such as toluene, xylene, n-paraffin, isoparaffin, dodecylbenzene, turpentine oil, kerosene or light oil; nitriles such as acetonitrile or propionitrile; amides such as acetamide or N,N-dimethylformamide; low molecular weight volatile silicone oil, or volatile organic modified silicone oil. Among these, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving handling and workability, the solvent of this embodiment more preferably includes esters, and even more preferably includes ethylene glycol monobutyl ether acetate. ;

[0058] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the content of the solvent in the conductive paste of this embodiment is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, even more preferably 0.5 mass % or more, and even more preferably 1 mass % or more, when the total amount of the conductive paste is 100 mass %, and is preferably 20 mass % or less, more preferably 10 mass % or less, even more preferably 5 mass % or less, even more preferably 3 mass % or less, and even more preferably 2 mass % or less.

[0059] <Preparation of conductive paste> The method for preparing the conductive paste is not particularly limited, but for example, the above-mentioned components are premixed, then kneaded using a three-roll mill, and further vacuum degassed to obtain a conductive paste. In this case, the long-term workability of the conductive paste can be improved by appropriately adjusting the preparation conditions, for example, by performing the premixing under reduced pressure.

[0060] <Glass transition temperature> The glass transition temperature of the conductive paste of this embodiment is, from the viewpoint of reducing the silver content and improving heat resistance while maintaining good conductivity in the conductive paste, preferably -50°C or higher, more preferably -40°C or higher, even more preferably -30°C or higher, even more preferably -25°C or higher, and is preferably 120°C or lower, more preferably 100°C or lower, even more preferably 90°C or lower, even more preferably 80°C or lower.

[0061] In this embodiment, the glass transition temperature of the conductive paste can be measured by, for example, the following method. First, the conductive paste obtained by the above method is applied to a Teflon (registered trademark) plate in a strip shape of 4 mm wide x 10 mm long x 150 μm thick, and the temperature is increased from 25 ° C to 175 ° C at a rate of 5 ° C / min, and then heated at 175 ° C for 5 hours to obtain a cured sample. Next, the obtained cured sample is peeled off from the Teflon (registered trademark) plate, and TMA (thermomechanical analysis) is measured using a TMA (thermomechanical analysis) device under the conditions of 30 to 200 ° C, 10 ° C / min, and 49 mN load for the first cycle, and -100 to 330 ° C, 10 ° C / min, and 49 mN load for the second cycle. The intersection of the tangent of the expansion curve from room temperature to the glass transition point in the second cycle and the tangent of the expansion curve after the glass transition point is the glass transition temperature.

[0062] <Viscosity> The viscosity of the conductive paste of this embodiment, measured using a BF viscometer at a temperature of 25°C and a rotation speed of 5 rpm, is preferably 0.1 Pa·s or more, more preferably 1 Pa·s or more, even more preferably 3 Pa·s or more, even more preferably 4 Pa·s or more, and is preferably 150 Pa·s or less, more preferably 120 Pa·s or less, even more preferably 100 Pa·s or less, and even more preferably 80 Pa·s or less, from the viewpoint of reducing the silver content and improving workability and application ability while maintaining good conductivity in the conductive paste. It is presumed that the viscosity of the conductive paste within the above range improves the dispersibility of the silver particles (b1) and alumina particles (b2), and improves the contact rate between the particles, thereby improving the conductivity of the conductive paste.

[0063] The viscosity of the conductive paste of this embodiment can be controlled by adjusting the type of thermosetting resin (A), the type of diluent, the amounts thereof, and the like.

[0064] In this embodiment, the viscosity of the conductive paste can be determined, for example, by measuring the viscosity of the conductive paste using a BF type viscometer at a measurement temperature of 25° C. and a rotation speed of 5 rpm.

[0065] In the conductive paste of this embodiment, when the viscosity measured at 25°C and 0.5 rpm using a BF type viscometer is η0.5, and the viscosity measured at 25°C and 5 rpm is η5, the thixotropy index, which is the viscosity ratio (η0.5 / η5), is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1 or more, even more preferably 1.4 or more, even more preferably 1.7 or more, even more preferably 2 or more, and is preferably 20 or less, more preferably 15 or less, even more preferably 10 or less, even more preferably 8 or less, even more preferably 6 or less, and even more preferably 5.5 or less, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving workability and application properties. It is presumed that the thixotropy index of the conductive paste within the above range improves the dispersibility of the silver particles (b1) and the alumina particles (b2), and improves the contact rate between the particles, thereby improving the conductivity of the conductive paste.

[0066] <Adhesion strength> From the viewpoint of improving the adhesiveness of the resulting conductive paste, the adhesive strength of the conductive paste of this embodiment with a silicon chip at 260°C is preferably 10 N or more, more preferably 20 N or more, even more preferably 30 N or more, even more preferably 40 N or more, and even more preferably 45 N or more, and the upper limit is not particularly limited, but may be 300 N or less, 250 N or less, 200 N or less, or 150 N or less. The failure mode of the above adhesive strength is preferably cohesive failure.

[0067] In this embodiment, the adhesion strength of the conductive paste can be measured, for example, by the following method. First, a conductive paste is applied onto a silver lead frame, then a silver-plated silicon chip measuring 2.0 mm long x 2.0 mm wide x 350±5 μm thick is placed on the conductive paste, and the temperature is raised from 25°C to 175°C over 30 minutes, and then heat-treated at 175°C for 1 hour to obtain a hardened body. The hardened body obtained is then used as a test piece, and the die shear strength of the silver lead frame and the silicon chip at 260°C and a shear speed of 500 μm / sec is measured for this test piece.

[0068] <Dynamic storage modulus> The dynamic storage modulus of the conductive paste of this embodiment at 25°C is preferably 300 MPa or more, more preferably 1000 MPa or more, even more preferably 1500 MPa or more, even more preferably 2000 MPa or more, even more preferably 2500 MPa or more, and preferably 30000 MPa or less, more preferably 27000 MPa or less, even more preferably 25000 MPa or less, and even more preferably 23000 MPa or less, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste. Similarly, the dynamic storage modulus at 250°C is preferably 10 MPa or more, more preferably 100 MPa or more, even more preferably 150 MPa or more, even more preferably 200 MPa or more, and preferably 2000 MPa or less, more preferably 1700 MPa or less, even more preferably 1400 MPa or less, and even more preferably 1100 MPa or less.

[0069] In this embodiment, the dynamic storage modulus of the conductive paste can be measured, for example, by the following method. First, the conductive paste is applied onto a Teflon (registered trademark) plate in a strip shape measuring 4 mm wide x 20 mm long x 300 μm thick, and the temperature is increased from 25° C. to 175° C. at a rate of 5° C. / min, and then heated at 175° C. for 1 hour to obtain a cured sample. The obtained cured sample is then peeled off from the Teflon (registered trademark) plate, and the dynamic storage modulus is measured under conditions of 25° C. (or 250° C.), tensile mode, and frequency of 10 Hz.

[0070] <cte> The average linear expansion coefficient (CTEα1) of the conductive paste of this embodiment, calculated from the slope of the tangent of the expansion curve from the measurement start temperature to the glass transition point at -100°C to 330°C, is preferably 5 ppm / °C or more, more preferably 10 ppm / °C or more, even more preferably 15 ppm / °C or more, even more preferably 20 ppm / °C or more, and is preferably 80 ppm / °C or less, more preferably 70 ppm / °C or less, even more preferably 60 ppm / °C or less, even more preferably 55 ppm / °C or less, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste. In addition, the average linear expansion coefficient (CTEα2) of the conductive paste of this embodiment, calculated from the slope of the tangent to the expansion curve after the glass transition point at -100°C to 330°C, is preferably 30 ppm / °C or more, more preferably 40 ppm / °C or more, even more preferably 50 ppm / °C or more, even more preferably 60 ppm / °C or more, and is preferably 200 ppm / °C or less, more preferably 180 ppm / °C or less, even more preferably 160 ppm / °C or less, even more preferably 150 ppm / °C or less.

[0071] In this embodiment, the CTE of the conductive paste can be measured by, for example, the following method. First, the conductive paste is applied on a Teflon (registered trademark) plate in a strip shape of 4 mm wide x 10 mm long x 150 μm thick, and the temperature is increased from 25 ° C to 175 ° C at a rate of 5 ° C / min, and then heated at 175 ° C for 5 hours to obtain a cured sample. The obtained cured sample is peeled off from the Teflon (registered trademark) plate, and TMA (thermomechanical analysis) is measured using a TMA (thermomechanical analysis) device under the conditions of 30 to 200 ° C, 10 ° C / min, and 49 mN load for the first cycle, and -100 to 330 ° C, 10 ° C / min, and 49 mN load for the second cycle. Then, the average linear expansion coefficient (CTE α 1) is calculated from the slope of the tangent of the expansion curve from the measurement start temperature to the glass transition point in the second cycle, and the average linear expansion coefficient (CTE α 2) is calculated from the slope of the tangent of the expansion curve after the glass transition point in the second cycle.

[0072] <Volume resistivity> The volume resistivity of the conductive paste of the present embodiment is preferably 9.0×10 from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste. -2 Ω cm or less, preferably 7.0×10 -2 Ω cm or less, more preferably 6.0×10 -2 The lower limit is not particularly limited, but is preferably 1.0×10 -6 It may be 1.0×10 Ω cm or more. -5 It may be 1.0×10 Ω cm or more. -4 It may be 1.0×10 Ω cm or more. -3 It may be Ω·cm or more.

[0073] In this embodiment, the volume resistivity of the conductive paste can be measured, for example, by the following method. The conductive paste is applied onto a glass plate in a strip shape measuring 4 mm wide x 40 mm long x 0.05 mm thick. The conductive paste coating layer is then heated from 25°C to 175°C at a heating rate of 5°C / min in a nitrogen atmosphere with a residual oxygen concentration of less than 1000 ppm, and then heat-treated at 175°C for 60 minutes to form a hardened layer of the conductive paste. The resistance of the hardened layer of the conductive paste is then measured by a DC four-electrode method using electrodes spaced 40 mm apart, and the volume resistivity is calculated.

[0074] <Conductive paste> The conductive paste of the present embodiment is preferably in a paste form at 20° C. That is, the conductive paste of the present embodiment can be applied to a substrate or the like in a paste-like manner at 20° C. This allows the conductive paste of the present embodiment to be preferably used as an adhesive for semiconductor elements or the like. Of course, depending on the process to be applied, the conductive paste of this embodiment may be in the form of a varnish having a relatively low viscosity.

[0075] <Application> The conductive paste according to the present embodiment is used, for example, to bond a substrate and a semiconductor element. Here, examples of the semiconductor element include a semiconductor package and an LED. In the present embodiment, LED stands for a light emitting diode.

[0076] Specific examples of semiconductor devices using LEDs include bullet-type LEDs, surface mount device (SMD) LEDs, COBs (Chip On Board), and power LEDs.

[0077] Specific types of the semiconductor packages include CMOS image sensors, hollow packages, Mold Array Packages (MAP), Quad Flat Packages (QFP), Small Outline Packages (SOP), Chip Size Packages (CSP), Quad Flat Non-leaded Packages (QFN), Small Outline Non-leaded Packages (SON), Ball Grid Arrays (BGA), Lead Flame BGAs (LF-BGA), Flip Chip BGAs (FC-BGA), Molded Array Process BGAs (MAP-BGA), Embedded Wafer-Level BGAs (eWLB), Fan-In type eWLB, and Fan-Out type eWLB.

[0078] <High thermal conductive materials> The highly thermally conductive material of the present embodiment includes a cured product of the conductive paste of the present embodiment. The highly thermally conductive material of the present embodiment can be obtained, for example, by sintering the conductive paste of the present embodiment. By changing the shape of the highly thermally conductive material, it can be applied to a variety of parts that require heat dissipation in the automotive and electrical fields.

[0079] <Semiconductor device> An example of a semiconductor device using the conductive paste according to this embodiment will be described below. FIG. 1 is a cross-sectional view showing a schematic example of a semiconductor device according to the present embodiment. The semiconductor device 100 of this embodiment includes a base material 30 and a semiconductor element 20 mounted on the base material 30 via an adhesive layer 10, and the adhesive layer 10 includes a hardened product of the conductive paste of this embodiment. The semiconductor element 20 and the base material 30 are electrically connected via, for example, a bonding wire 40 or the like. The semiconductor element 20 is sealed with, for example, a sealing resin 50.

[0080] 1, the base material 30 is, for example, a lead frame. In this case, the semiconductor element 20 is mounted on the die pad 32 or the base material 30 via an adhesive layer 10. The semiconductor element 20 is also electrically connected to an outer lead 34 (base material 30) via, for example, a bonding wire 40. The base material 30, which is a lead frame, is made of, for example, a 42 alloy or a Cu frame.

[0081] The semiconductor device of the present embodiment can be manufactured by using the conductive paste of the present embodiment. For example, the semiconductor device of the present embodiment can be manufactured by using the conductive paste of the present embodiment as an "adhesive" between a substrate and a semiconductor element.

[0082] In other words, the semiconductor device of this embodiment includes, for example, a base material and a semiconductor element mounted on the base material via an adhesive layer obtained by sintering the above-mentioned conductive paste through a heat treatment. In the semiconductor device of this embodiment, the adhesiveness of the adhesive layer is not easily deteriorated even by heat cycles, which means that the reliability of the semiconductor device of this embodiment is high. Examples of semiconductor elements include ICs, LSIs, power semiconductor elements (power semiconductors), and various other elements. Examples of the substrate include various semiconductor wafers, lead frames, BGA substrates, mounting substrates, heat spreaders, heat sinks, and the like.

[0083] <More preferred embodiment> Hereinafter, a more preferred embodiment (first embodiment) of the present invention in which the thermosetting resin (A) contains an epoxy resin (a1), and a more preferred embodiment (second embodiment) of the present invention in which the thermosetting resin (A) contains a (meth)acrylic resin (a2) will be described.

[0084] [First embodiment] The thermosetting resin (A) of this embodiment contains an epoxy resin (a1), and the conductive paste of this embodiment further contains a (meth)acrylate compound.

[0085] The conductive paste of the present embodiment contains the epoxy resin (a1) and the (meth)acrylate compound, and thus can suppress the cure shrinkage of the conductive paste.

[0086] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the thermosetting resin (A) in the conductive paste of this embodiment is preferably 1 mass % or more, more preferably 3 mass % or more, even more preferably 5 mass % or more, even more preferably 7 mass % or more, even more preferably 9 mass % or more, even more preferably 11 mass % or more, and is preferably 20 mass % or less, more preferably 17 mass % or less, even more preferably 15 mass % or less, and even more preferably 13 mass % or less, when the total amount of the conductive paste is 100 mass %.

[0087] <Epoxy resin (a1)> The epoxy resin (a1) used as the thermosetting resin (A) of this embodiment can be a monomer, oligomer, or polymer having two or more glycidyl groups in one molecule, and its molecular weight or molecular structure is not particularly limited. The epoxy resin (a1) of this embodiment can be, for example, a biphenyl type epoxy resin; a bisphenol type epoxy resin such as a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, a tetramethyl bisphenol F type epoxy resin, a modified bisphenol A type epoxy resin, or a modified bisphenol F type epoxy resin; a stilbene type epoxy resin; a novolac type epoxy resin such as a phenol novolac type epoxy resin or a cresol novolac type epoxy resin; a multifunctional epoxy resin such as a triphenol methane type epoxy resin or an alkyl-modified triphenol methane type epoxy resin; an aralkyl type epoxy resin such as a phenol aralkyl type epoxy resin having a phenylene skeleton or a phenol aralkyl type epoxy resin having a biphenylene skeleton; a naphthol type epoxy resin such as a dihydroxynaphthalene type epoxy resin or an epoxy resin obtained by glycidyl etherifying a dimer of dihydroxynaphthalene; a triglycidyl isopropyl epoxy resin; It is preferable that the epoxy resin contains one or more selected from the group consisting of triazine nucleus-containing epoxy resins such as triazine nucleus-containing epoxy resins containing cyanurate and monoallyl diglycidyl isocyanurate; phenol-type epoxy resins modified with a bridged cyclic hydrocarbon compound such as dicyclopentadiene-modified phenol-type epoxy resins; diglycidyl ethers of bisphenol compounds such as bisphenol A, bisphenol F, biphenol, etc. or derivatives thereof; diglycidyl ethers of diols having an alicyclic structure such as hydrogenated bisphenol A, hydrogenated bisphenol F, hydrogenated biphenol, cyclohexanediol, cyclohexanedimethanol, cyclohexanediethanol, etc. or derivatives thereof; diglycidyl ethers of aliphatic diols such as butanediol, hexanediol, octanediol, nonanediol, decanediol, etc. or derivatives thereof; and triglycidyl ethers having a trihydroxyphenylmethane skeleton or an aminophenol skeleton.

[0088] Among these, from the viewpoint of improving the coating workability and adhesiveness of the obtained conductive paste, the epoxy resin (a1) of this embodiment more preferably contains one or more selected from the group consisting of bisphenol type epoxy resins and diglycidyl ethers of diols having an alicyclic structure, and further preferably contains one or more selected from the group consisting of bisphenol F type epoxy resins, modified bisphenol A type epoxy resins, and diglycidyl ethers of cyclohexanediol. Also, from the viewpoint of more effectively improving the coating workability of the conductive paste, the epoxy resin (a1) of this embodiment preferably contains a liquid epoxy resin that is liquid at 25°C.

[0089] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to a substrate, the content of the epoxy resin (a1) in the conductive paste of this embodiment is preferably 1 mass % or more, more preferably 3 mass % or more, even more preferably 5 mass % or more, even more preferably 7 mass % or more, even more preferably 9 mass % or more, even more preferably 11 mass % or more, and is preferably 20 mass % or less, more preferably 17 mass % or less, even more preferably 15 mass % or less, and even more preferably 13 mass % or less, when the total amount of the conductive paste is taken as 100 mass %.

[0090] <(Meth)acrylate compounds> The conductive paste of this embodiment contains a (meth)acrylate compound as a diluent, which gives the conductive paste of this embodiment a viscosity suitable for achieving application to a substrate and filling into fine details.

[0091] From the viewpoints of reducing the silver content while maintaining good electrical conductivity in the conductive paste and improving the applicability to the substrate and the ability to fill in fine details, the (meth)acrylate compound of the present embodiment preferably contains one or more monomers selected from the group consisting of monofunctional (meth)acrylic monomers having only one (meth)acrylic group and polyfunctional (meth)acrylic monomers having two or more (meth)acrylic groups, and more preferably contains a polyfunctional (meth)acrylic monomer.

[0092] The (meth)acrylate compound of the present embodiment may be a polyfunctional (meth)acrylic monomer, such as ethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, hexane-1,6-diol bis(2-methyl(meth)acrylate), 4,4'-isopropylidenediphenol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3 ,3,4,4,5,5-octafluorohexane, 1,4-bis((meth)acryloyloxy)butane, 1,6-bis((meth)acryloyloxy)hexane, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, N,N'-(1,2-dihydroxyethylene)bis(meth)acrylamide, and 1,4-bis((meth)acryloyl)piperazine. Among these, from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the applicability to the substrate and the filling ability into fine details, it is more preferable that the (meth)acrylate compound of this embodiment contains ethylene glycol di(meth)acrylate.

[0093] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the (meth)acrylate compound in the conductive paste of this embodiment is preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 2 mass% or more, even more preferably 2.5 mass% or more, even more preferably 3 mass% or more, even more preferably 3.5 mass% or more, even more preferably 4 mass% or more, even more preferably 4.5 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 8 mass% or less, even more preferably 7 mass% or less, and even more preferably 6 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0094] <Hardening agent> The conductive paste of the present embodiment preferably contains a curing agent. This can improve the curing property of the conductive paste. The curing agent of the present embodiment contains, for example, one or more selected from the group consisting of acid anhydrides and phenolic compounds. Among these, from the viewpoint of improving the curing property and manufacturing stability of the conductive paste, the curing agent of the present embodiment preferably contains a phenolic compound.

[0095] The phenol compound used as the curing agent of this embodiment is a compound having two or more phenolic hydroxyl groups in one molecule. The number of phenolic hydroxyl groups in one molecule is preferably 2 to 5, more preferably 2 to 4, even more preferably 2 to 3, and even more preferably 2. This can more effectively improve the coating workability of the conductive paste, and can form a crosslinked structure during curing to provide excellent cured product properties of the conductive paste. The phenol compound may include one or more selected from the group consisting of bisphenols such as bisphenol F, bisphenol A, bisphenol S, tetramethyl bisphenol A, tetramethyl bisphenol F, tetramethyl bisphenol S, dihydroxydiphenyl ether, dihydroxybenzophenone, tetramethyl biphenol, ethylidene bisphenol, methyl ethylidene bis(methylphenol), cyclohexylidene bisphenol, and biphenol, trifunctional phenols such as tri(hydroxyphenyl)methane and tri(hydroxyphenyl)ethane, and compounds obtained by reacting phenols such as phenol novolac and cresol novolac with formaldehyde, which are mainly binuclear or trinuclear, and derivatives thereof. Among these, from the viewpoint of improving the curability and manufacturing stability of the conductive paste, it is more preferable that the curing agent of the present embodiment includes one or more phenol compounds selected from the group consisting of bisphenols and derivatives thereof, and more preferably includes bisphenol F.

[0096] From the viewpoint of reducing the silver content and improving the curing property while maintaining good conductivity in the conductive paste, the content of the curing agent in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, even more preferably 2 mass% or more, even more preferably 2.5 mass% or more, even more preferably 3 mass% or more, even more preferably 3.5 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 8 mass% or less, even more preferably 7 mass% or less, even more preferably 6 mass% or less, and even more preferably 5 mass% or less.

[0097] <Coupling Agent> The conductive paste of the present embodiment preferably contains a coupling agent, which can improve the adhesion between the conductive paste and the substrate. Examples of the coupling agent of the present embodiment include vinyl silanes such as vinyl trimethoxy silane and vinyl triethoxy silane; epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyl trimethoxy silane, 3-glycidyloxypropyl trimethoxy silane, 3-glycidoxypropyl methyl dimethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-glycidoxypropyl methyl diethoxy silane, and 3-glycidoxypropyl triethoxy silane; styryl silanes such as p-styryl trimethoxy silane; methacryl silanes such as 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, and 3-methacryloxypropyl triethoxy silane; and acryl silanes such as 3-(trimethoxysilyl)propyl methacrylate and 3-acryloxypropyl trimethoxy silane. silanes such as N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, and N-phenyl-γ-aminopropyltrimethoxysilane; isocyanurate silanes; alkyl silanes; ureido silanes such as 3-ureidopropyltrialkoxysilane; mercapto silanes such as 3-mercaptopropylmethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane; isocyanate silanes such as 3-isocyanatepropyltriethoxysilane; and polysulfide silanes such as bis(3-(triethoxysilyl)propyl)tetrasulfide. Among these, from the viewpoint of improving the adhesion between the conductive paste and the substrate, the coupling agent of the present embodiment more preferably contains one or more types selected from the group consisting of epoxy silanes and polysulfide-based silanes, and even more preferably contains one or two types selected from the group consisting of 3-glycidyloxypropyltrimethoxysilane and bis(3-(triethoxysilyl)propyl)tetrasulfide.

[0098] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, the content of the coupling agent in the conductive paste of this embodiment is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, even more preferably 0.2 mass% or more, even more preferably 0.3 mass% or more, even more preferably 0.4 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 2 mass% or less, and even more preferably 1 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0099] <Curing aid> The conductive paste of this embodiment preferably contains a curing aid. This can promote the reaction between the epoxy resin (a1) and the curing agent. The curing aid of this embodiment preferably contains one or more selected from the group consisting of phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines such as dicyandiamide, 2-phenyl-4,5-dihydroxymethylimidazole, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine, tertiary amines and their derivatives; and nitrogen atom-containing compounds such as quaternary ammonium salts of the amidines or tertiary amines. Among these, from the viewpoint of further promoting the reaction between the epoxy resin (a1) and the curing agent, the curing aid of the present embodiment more preferably contains one or more selected from the group consisting of amidines, tertiary amines and derivatives thereof, and further preferably contains one or more selected from the group consisting of dicyandiamide derivatives and 2-phenyl-4,5-dihydroxymethylimidazole.

[0100] From the viewpoint of further promoting the reaction between the epoxy resin (a1) and the curing agent, the content of the curing aid in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 0.001 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, and even more preferably 0.15 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 2 mass% or less, even more preferably 1 mass% or less, and even more preferably 0.5 mass% or less.

[0101] <Radical polymerization initiator> The conductive paste of the present embodiment preferably contains a radical polymerization initiator. This may, for example, prevent insufficient curing, allow the curing reaction to proceed sufficiently at a relatively low temperature (e.g., 180°C), or further improve the adhesive strength. From the viewpoint of allowing the curing reaction to proceed sufficiently, the radical initiator of the present embodiment preferably contains one or two selected from the group consisting of peroxides and azo compounds, and more preferably contains a peroxide.

[0102] From the viewpoint of sufficiently progressing the curing reaction, the radical polymerization initiator of the present embodiment preferably contains, as the peroxide, an organic peroxide such as a diacyl peroxide, a dialkyl peroxide, or a peroxyketal, and examples of such organic peroxides include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane and 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane; hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide; di(2-t-butylperoxyisopropyl)benzene and dicumyl peroxide; peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate; and peroxyesters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-hexyl peroxybenzoate, t-butylperoxy 2-ethylhexanoate. Among these, from the viewpoint of sufficiently progressing the curing reaction, the radical polymerization initiator of the present embodiment more preferably contains 1,1-di(t-butylperoxy)cyclohexane.

[0103] From the viewpoint of allowing the curing reaction to proceed sufficiently, the content of the radical polymerization initiator in the conductive paste of this embodiment, when the total amount of the conductive paste is taken as 100 mass%, is preferably 0.001 mass% or more, more preferably 0.005 mass% or more, even more preferably 0.01 mass% or more, even more preferably 0.05 mass% or more, even more preferably 0.09 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 1 mass% or less, and even more preferably 0.5 mass% or less.

[0104] <Other ingredients> The conductive paste of this embodiment preferably contains, as other components, silver particles (b1), alumina particles (b2), an inorganic filler, and a solvent, as described above.

[0105] <Glass transition temperature> From the viewpoint of reducing the silver content and improving heat resistance while maintaining good conductivity in the conductive paste, the glass transition temperature of the conductive paste of this embodiment is preferably −50° C. or higher, more preferably 0° C. or higher, even more preferably 20° C. or higher, even more preferably 40° C. or higher, even more preferably 50° C. or higher, even more preferably 60° C. or higher, and preferably 120° C. or lower, more preferably 110° C. or lower, even more preferably 100° C. or lower, even more preferably 90° C. or lower, even more preferably 80° C. or lower. The glass transition temperature is measured by the method described above.

[0106] <Dynamic storage modulus> From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the dynamic storage modulus of the conductive paste of this embodiment at 25°C is preferably 300 MPa or more, more preferably 3000 MPa or more, more preferably 7000 MPa or more, more preferably 10000 MPa or more, more preferably 13000 MPa or more, more preferably 15000 MPa or more, and preferably 30000 MPa or less, more preferably 27000 MPa or less, more preferably 25000 MPa or less, more preferably 24000 MPa or less, and more preferably 23000 MPa or less. Similarly, the dynamic storage modulus of the conductive paste of this embodiment at 250°C is preferably 10 MPa or more, more preferably 100 MPa or more, more preferably 200 MPa or more, more preferably 250 MPa or more, more preferably 300 MPa or more, and preferably 2000 MPa or less, more preferably 1500 MPa or less, more preferably 1000 MPa or less, more preferably 800 MPa or less, more preferably 600 MPa or less, and more preferably 500 MPa or less. The dynamic storage modulus is measured by the method described above.

[0107] <Other physical properties> The conductive paste of this embodiment preferably has other physical properties, such as viscosity, thixotropy index, adhesion strength, CTE, and volume resistivity, within the ranges described above.

[0108] [Second embodiment] The thermosetting resin (A) of this embodiment contains a (meth)acrylic resin (a2), and the conductive paste of this embodiment further contains a (meth)acrylate compound and a stress reducing agent.

[0109] The conductive paste of the present embodiment contains the (meth)acrylic resin (a2), the (meth)acrylate compound, and the stress reducing agent, and thus the dynamic storage modulus of the conductive paste can be reduced.

[0110] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the thermosetting resin (A) in the conductive paste of this embodiment is preferably 1 mass % or more, more preferably 2 mass % or more, even more preferably 2.5 mass % or more, even more preferably 3 mass % or more, and even more preferably 3.5 mass % or more, when the total amount of the conductive paste is 100 mass %, and is preferably 20 mass % or less, more preferably 15 mass % or less, even more preferably 10 mass % or less, and even more preferably 8 mass % or less.

[0111] <(Meth)acrylic resin (a2)> The (meth)acrylic resin (a2) used as the thermosetting resin (A) in this embodiment may be, from the viewpoint of improving the storage stability of the obtained conductive paste, for example, a methyl(meth)acrylate type (meth)acrylic resin, an ethyl(meth)acrylate type (meth)acrylic resin, a propyl(meth)acrylate type (meth)acrylic resin, a butyl(meth)acrylate type (meth)acrylic resin, a 2-ethylhexyl(meth)acrylate type (meth)acrylic resin, a lauryl(meth)acrylate type (meth)acrylic resin, a stearyl(meth)acrylate type (meth)acrylic resin, a cyclohexyl(meth)acrylate type (meth)acrylic resin, a 2-hydroxyethyl(meth)acrylate type (meth)acrylic resin, a 2-propyl(meth)acrylate type (meth)acrylic resin, a 2-phenyl ... It is preferable that the (meth)acrylic resin (a2) of this embodiment contains one or more selected from the group consisting of ethyl (meth)acrylate type (meth)acrylic resin, chloro-2-hydroxyethyl (meth)acrylate type (meth)acrylic resin, ethylene glycol di(meth)acrylate type (meth)acrylic resin, diethylene glycol mono(meth)acrylate type (meth)acrylic resin, methoxyethyl (meth)acrylate type (meth)acrylic resin, glycidyl (meth)acrylate type (meth)acrylic resin, 1,4-cyclohexanedimethanol mono(meth)acrylate type (meth)acrylic resin, dicyclopentanyl (meth)acrylate type (meth)acrylic resin, dicyclopentenyl (meth)acrylate type (meth)acrylic resin and isoboronol (meth)acrylate type (meth)acrylic resin. Among these, from the viewpoint of improving the storage stability of the obtained conductive paste, it is more preferable that the (meth)acrylic resin (a2) of this embodiment contains a glycidyl (meth)acrylate type (meth)acrylic resin.

[0112] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to a substrate, the content of the (meth)acrylic resin (a2) in the conductive paste of this embodiment is preferably 1 mass % or more, more preferably 2 mass % or more, even more preferably 2.5 mass % or more, even more preferably 3 mass % or more, and even more preferably 3.5 mass % or more, when the total amount of the conductive paste is 100 mass %, and is preferably 20 mass % or less, more preferably 15 mass % or less, even more preferably 10 mass % or less, and even more preferably 8 mass % or less.

[0113] <(Meth)acrylate compounds> The conductive paste of this embodiment contains a (meth)acrylate compound as a diluent, which gives the conductive paste of this embodiment a viscosity suitable for achieving application to a substrate and filling into fine details.

[0114] From the viewpoints of reducing the silver content while maintaining good electrical conductivity in the conductive paste and improving the applicability to the substrate and the ability to fill in fine details, the (meth)acrylate compound of the present embodiment preferably contains one or more monomers selected from the group consisting of monofunctional (meth)acrylic monomers having only one (meth)acrylic group and polyfunctional (meth)acrylic monomers having two or more (meth)acrylic groups, and more preferably contains both a monofunctional (meth)acrylic monomer and a polyfunctional (meth)acrylic monomer.

[0115] In the (meth)acrylate compound of the present embodiment, from the viewpoint of reducing the silver content while having good conductivity in a conductive paste and improving the applicability to a substrate and the ability to fill in fine areas, as a monofunctional (meth)acrylic monomer, for example, 2-phenoxyethyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tridecyl (meth)acrylate, n-stearyl (meth)acrylate, isostearyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, butoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 2-ethyl Hexyl diethylene glycol (meth)acrylate, methoxy polyethylene glycol (meth)acrylate, methoxy dipropylene glycol (meth)acrylate, cyclohexyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy diethylene glycol (meth)acrylate, phenoxy polyethylene glycol (meth)acrylate, nonylphenol ethylene oxide modified (meth)acrylate, phenylphenol ethylene oxide modified (meth)acrylate, isobornyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate quaternized, glycidyl (meth)acrylate, neopentyl glycol (meth)acrylic acid benzoate, 1,It is preferable that the compound contains one or more selected from the group consisting of 4-cyclohexanedimethanol mono(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, 2-hydroxy-3-phenoxypropyl(meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalic acid, 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloyloxyethyl acid phosphate, and polyoxypropylene monomethacrylate. Among these, from the viewpoint of reducing the silver content while maintaining good electrical conductivity in the conductive paste and improving the applicability to the substrate and the filling ability in fine areas, it is more preferable that the (meth)acrylate compound of the present embodiment contains one or more compounds selected from the group consisting of 2-phenoxyethyl (meth)acrylate and polyoxypropylene monomethacrylate.

[0116] In addition, in the (meth)acrylate compound of the present embodiment, from the viewpoint of reducing the silver content while maintaining good conductivity in a conductive paste and improving the applicability to a substrate and the ability to fill in fine areas, polyfunctional (meth)acrylic monomers such as ethylene glycol di(meth)acrylate, 1,6-hexanediol dimethacrylate, trimethylolpropane tri(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, hexane-1,6-diol bis(2-methyl(meth)acrylate), 4,4'-isopropylidenediphenol di(meth)acrylate, , 1,3-butanediol di(meth)acrylate, 1,6-bis((meth)acryloyloxy)-2,2,3,3,4,4,5,5-octafluorohexane, 1,4-bis((meth)acryloyloxy)butane, triethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, N,N'-di(meth)acryloylethylenediamine, N,N'-(1,2-dihydroxyethylene)bis(meth)acrylamide and 1,4-bis((meth)acryloyl)piperazine. Among these, from the viewpoint of reducing the silver content while having good conductivity in the conductive paste and improving the application property to the substrate and the filling property in the fine details, the (meth)acrylate compound of the present embodiment is more preferably one or two or more selected from the group consisting of ethylene glycol di(meth)acrylate and 1,6 hexanediol dimethacrylate.

[0117] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the (meth)acrylate compound in the conductive paste of this embodiment is preferably 0.1 mass % or more, more preferably 1 mass % or more, even more preferably 3 mass % or more, even more preferably 5 mass % or more, even more preferably 7 mass % or more, even more preferably 9 mass % or more, and is preferably 40 mass % or less, more preferably 30 mass % or less, even more preferably 25 mass % or less, and even more preferably 20 mass % or less, when the total amount of the conductive paste is 100 mass %.

[0118] In addition, the (meth)acrylate compound of the present embodiment preferably contains a long-chain (meth)acrylic monomer from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate. Here, the molecular weight of the long-chain (meth)acrylic monomer is preferably 300 or more, more preferably 400 or more, even more preferably 500 or more, even more preferably 600 or more, even more preferably 700 or more, even more preferably 800 or more, and preferably 2000 or less, more preferably 1700 or less, even more preferably 1400 or less, even more preferably 1200 or less, even more preferably 1000 or less, even more preferably 900 or less. In addition, the (meth)acrylate compound of the present embodiment preferably contains polyoxypropylene monomethacrylate as the long-chain (meth)acrylic monomer from the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate.

[0119] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving the balance of various properties such as adhesion to the substrate, the content of the long-chain (meth)acrylic monomer in the conductive paste of this embodiment is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, even more preferably 0.5 mass% or more, even more preferably 1 mass% or more, even more preferably 1.5 mass% or more, even more preferably 2 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 8 mass% or less, and even more preferably 6 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0120] <Low stress agent> The conductive paste of the present embodiment includes a low stress agent. This can improve the low stress properties of the conductive paste. From the viewpoint of reducing the silver content and improving the low stress properties while maintaining good conductivity in the conductive paste, the low stress agent of the present embodiment preferably includes one or more selected from the group consisting of silicone compounds such as silicone oil and silicone rubber; polybutadiene compounds such as polybutadiene maleic anhydride adducts; acrylic acid polymers such as acrylonitrile butadiene copolymer compounds, and allyl ester resins, more preferably includes a polybutadiene compound, and even more preferably includes a polybutadiene maleic anhydride adduct.

[0121] From the viewpoint of reducing the silver content and improving low stress properties while maintaining good conductivity in the conductive paste, the content of the low stress agent in the conductive paste of this embodiment is preferably 0.001 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.03 mass% or more, even more preferably 0.05 mass% or more, even more preferably 0.07 mass% or more, even more preferably 0.09 mass% or more, and is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 7 mass% or less, even more preferably 5 mass% or less, and even more preferably 3 mass% or less, when the total amount of the conductive paste is 100 mass%.

[0122] <Coupling Agent> The conductive paste of the present embodiment preferably contains a coupling agent, which can improve the adhesion between the conductive paste and the substrate. In terms of improving the adhesion between the conductive paste and the base material, examples of the coupling agent of the present embodiment include vinyl silanes such as vinyl trimethoxy silane and vinyl triethoxy silane; epoxy silanes such as 2-(3,4-epoxycyclohexyl)ethyl trimethoxy silane, 3-glycidyloxypropyl trimethoxy silane, 3-glycidoxypropyl methyl dimethoxy silane, 3-glycidoxypropyl trimethoxy silane, 3-glycidoxypropyl methyl diethoxy silane, and 3-glycidoxypropyl triethoxy silane; styryl silanes such as p-styryl trimethoxy silane; methacryl silanes such as 3-methacryloxypropyl methyl dimethoxy silane, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl methyl diethoxy silane, and 3-methacryloxypropyl triethoxy silane; 3-(trimethoxysilyl)propyl methacrylate, 3-acryloxypropyl trimethoxy silane, and the like. It is preferable to include one or more selected from the group consisting of acrylic silanes such as trimethoxysilane; amino silanes such as N-2-(aminoethyl)-3-aminopropyl methyl dimethoxy silane, N-2-(aminoethyl)-3-aminopropyl trimethoxy silane, 3-aminopropyl trimethoxy silane, 3-aminopropyl triethoxy silane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene) propylamine, and N-phenyl-γ-aminopropyl trimethoxy silane; isocyanurate silanes; alkyl silanes; ureido silanes such as 3-ureidopropyl trialkoxy silane; mercapto silanes such as 3-mercaptopropyl methyl dimethoxy silane and 3-mercaptopropyl trimethoxy silane; isocyanate silanes such as 3-isocyanate propyl triethoxy silane; and polysulfide silanes such as bis(3-(triethoxysilyl)propyl) tetrasulfide.Among these, from the viewpoint of improving the adhesion between the conductive paste and the substrate, the coupling agent of the present embodiment more preferably contains an epoxy silane, and even more preferably contains one or more selected from the group consisting of 3-glycidyloxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane.

[0123] From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste and improving adhesion to the substrate, the content of the coupling agent in the conductive paste of this embodiment is preferably 0 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.1 mass% or more, and even more preferably 0.2 mass% or more, when the total amount of the conductive paste is 100 mass%, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 2 mass% or less, and even more preferably 1 mass% or less.

[0124] <Curing aid> The conductive paste of this embodiment preferably contains a curing aid. This can accelerate the curing reaction of the (meth)acrylic resin (a2). From the viewpoint of further accelerating the curing reaction of the (meth)acrylic resin (a2), the curing aid of this embodiment preferably contains one or more selected from the group consisting of phosphorus atom-containing compounds such as organic phosphines, tetra-substituted phosphonium compounds, phosphobetaine compounds, adducts of phosphine compounds and quinone compounds, and adducts of phosphonium compounds and silane compounds; amidines such as dicyandiamide, 2-phenyl-4,5-dihydroxymethylimidazole, 1,8-diazabicyclo[5.4.0]undecene-7, and benzyldimethylamine; tertiary amines and derivatives thereof; and nitrogen atom-containing compounds such as quaternary ammonium salts of the amidines or tertiary amines. It is more preferable to contain one or more selected from the group consisting of amidines, tertiary amines and derivatives thereof, and it is even more preferable to contain a dicyandiamide derivative.

[0125] From the viewpoint of further promoting the curing reaction of the (meth)acrylic resin (a2), the content of the curing aid in the conductive paste of this embodiment is, when the total amount of the conductive paste is taken as 100 mass%, preferably 0 mass% or more, more preferably 0.01 mass% or more, even more preferably 0.03 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 1 mass% or less, and even more preferably 0.5 mass% or less.

[0126] <Radical polymerization initiator> The conductive paste of the present embodiment preferably contains a radical polymerization initiator. This may, for example, prevent insufficient curing, allow the curing reaction to proceed sufficiently at a relatively low temperature (e.g., 180°C), and further improve the adhesive strength. From the viewpoint of allowing the curing reaction to proceed sufficiently, the radical initiator of the present embodiment preferably contains one or more selected from the group consisting of peroxides and azo compounds, and more preferably contains a peroxide.

[0127] From the viewpoint of sufficiently progressing the curing reaction, the radical polymerization initiator of the present embodiment preferably contains, as the peroxide, an organic peroxide such as a diacyl peroxide, a dialkyl peroxide, or a peroxyketal, and examples of such organic peroxides include ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide; peroxyketals such as 1,1-di(t-butylperoxy)cyclohexane and 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane; hydroperoxides such as p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, and t-butyl hydroperoxide; di(2-t-butylperoxyisopropyl)benzene and dicumyl peroxide; It is more preferable that the radical polymerization initiator of the present embodiment contains one or more selected from the group consisting of dialkyl peroxides such as 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, and di-t-butyl peroxide; diacyl peroxides such as dibenzoyl peroxide and di(4-methylbenzoyl)peroxide; peroxydicarbonates such as di-n-propyl peroxydicarbonate and diisopropyl peroxydicarbonate; and peroxyesters such as 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-hexyl peroxybenzoate, t-butyl peroxybenzoate, and t-butylperoxy 2-ethylhexanoate. Among these, from the viewpoint of sufficiently proceeding with the curing reaction, it is more preferable that the radical polymerization initiator of the present embodiment contains dicumyl peroxide.

[0128] From the viewpoint of allowing the curing reaction to proceed sufficiently, the content of the radical polymerization initiator in the conductive paste of this embodiment, when the total amount of the conductive paste is taken as 100 mass%, is preferably 0.001 mass% or more, more preferably 0.005 mass% or more, even more preferably 0.01 mass% or more, even more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 3 mass% or less, even more preferably 2 mass% or less, and even more preferably 1 mass% or less.

[0129] <Other ingredients> The conductive paste of this embodiment preferably contains, as other components, silver particles (b1), alumina particles (b2), an inorganic filler, and a solvent, as described above.

[0130] <Glass transition temperature> From the viewpoint of reducing the silver content and improving heat resistance while maintaining good conductivity in the conductive paste, the glass transition temperature of the conductive paste of this embodiment is preferably −50° C. or higher, more preferably −40° C. or higher, even more preferably −35° C. or higher, even more preferably −30° C. or higher, even more preferably −25° C. or higher, and preferably 120° C. or lower, more preferably 100° C. or lower, even more preferably 80° C. or lower, even more preferably 60° C. or lower, even more preferably 50° C. or lower. The glass transition temperature is measured by the method described above.

[0131] <Dynamic storage modulus> From the viewpoint of reducing the silver content while maintaining good conductivity in the conductive paste, the dynamic storage modulus of the conductive paste of this embodiment at 25°C is preferably 300 MPa or more, more preferably 1000 MPa or more, even more preferably 1500 MPa or more, even more preferably 2000 MPa or more, even more preferably 2500 MPa or more, and preferably 30000 MPa or less, more preferably 20000 MPa or less, even more preferably 15000 MPa or less, even more preferably 10000 MPa or less, even more preferably 7000 MPa or less, even more preferably 5000 MPa or less. Similarly, the dynamic storage modulus of the conductive paste of this embodiment at 250°C is preferably 10 MPa or more, more preferably 100 MPa or more, even more preferably 150 MPa or more, even more preferably 200 MPa or more, and preferably 2000 MPa or less, more preferably 1700 MPa or less, even more preferably 1500 MPa or less, even more preferably 1300 MPa or less, even more preferably 1200 MPa or less, even more preferably 1100 MPa or less. The dynamic storage modulus is measured by the method described above.

[0132] <Other physical properties> The conductive paste of this embodiment preferably has other physical properties, such as viscosity, thixotropy index, adhesion strength, CTE, and volume resistivity, within the ranges described above. EXAMPLES

[0133] [Preparation of conductive paste] The components were premixed according to the formulation shown in Table 1, then kneaded using a triple roll and vacuum degassed to prepare a conductive paste. The content of each component in Table 1 is expressed in parts by mass.

[0134] The details of the components shown in Table 1 are as follows:

[0135] <Epoxy resin (a1)> Epoxy resin a1-1: SB-403S (bisphenol F type epoxy resin, manufactured by Nippon Kayaku Co., Ltd.) Epoxy resin a1-2: EXA-4850-1000 (modified bisphenol A type epoxy resin, manufactured by Dainippon Ink Co., Ltd.) Epoxy resin a1-3: ZX-1658GS (diglycidyl ether of cyclohexanediol, manufactured by Nippon Steel Corporation)

[0136] <(Meth)acrylic resin (a2)> Acrylic resin a2-1: UG-4035 (glycidyl (meth)acrylate type (meth)acrylic resin, manufactured by Toagosei Co., Ltd.)

[0137] <(Meth)acrylate compounds> (Meth)acrylate compound 1: Light Ester EG (molecular weight 198, ethylene glycol dimethacrylate, manufactured by Kyoeisha Chemical Co., Ltd.) (Meth)acrylate compound 2: Light Ester PO (molecular weight 206, 2-phenoxyethyl methacrylate, manufactured by Kyoeisha Chemical Co., Ltd.) (Meth)acrylate compound 3: Blenmer PP800 (molecular weight 841, polyoxypropylene monomethacrylate, manufactured by NOF Corporation)

[0138] <Low stress agent> Low stress agent 1: Ricobond 1731 (number average molecular weight 5400, polybutadiene maleic anhydride adduct, manufactured by SARTOMER COMPANY (now Cray Valley))

[0139] <Hardening agent> Hardener 1: DIC-BPF (Bisphenol F, manufactured by DIC)

[0140] <Coupling Agent> Coupling agent 1: Bis(3-(triethoxysilyl)propyl)tetrasulfide Coupling agent 2: 3-methacryloxypropyltrimethoxysilane

[0141] <Curing aid> -Curing agent 1: 2-phenyl-4,5-dihydroxymethylimidazole)

[0142] <Radical polymerization initiator> Radical polymerization initiator 1: 1,1-di(t-butylperoxy)cyclohexane Radical polymerization initiator 2: Dicumyl peroxide

[0143] <Silver particles (b1)> Silver particles b1-1: HKD-11 (flake-shaped particles, average particle size D 50 : 2.5μm, Fukuda Metal Foil Powder Co., Ltd.) Silver particles b1-2: HKD-10A (flake-shaped particles, average particle size D 50 : 8μm, Fukuda Metal Foil Powder Co., Ltd.) Silver particles b1-3: TKR-88 (flake particles, average particle size D 50 : 3.3μm, Tokuriki Honten Co., Ltd.) Silver particles b1-4: TKR-20A (flake-shaped particles, average particle size D 50 : 8μm, Tokuriki Honten Co., Ltd.)

[0144] <Alumina particles (b2)> ·Alumina particles b2-1: DAW-0310 (spherical particles, average particle size D 50 :3.2μm)

[0145] [Physical property evaluation] <Average particle size D 50 Measurement> The average particle size D of the above silver particles (b1) and alumina particles (b2) 50 was obtained by particle image measurement using a flow particle image analyzer FPIA (registered trademark)-3000 manufactured by Sysmex Corporation. More specifically, the particle sizes of the silver particles (b1) and the alumina particles (b2) were determined by measuring the volume-based median diameter in a wet manner using this device.

[0146] <Glass transition temperature measurement> The conductive paste obtained by the above method was applied on a Teflon (registered trademark) plate in a strip shape of 4 mm wide x 10 mm long x 150 μm thick, and the temperature was raised from 25 ° C to 175 ° C at a heating rate of 5 ° C / min, and then heated at 175 ° C for 5 hours to obtain a cured sample. The obtained cured sample was peeled off from the Teflon (registered trademark) plate, and TMA (thermomechanical analysis) was measured using a TMA (thermomechanical analysis) device (SII SS7100, manufactured by Hitachi High-Tech Science Corporation) under the conditions of 30 to 200 ° C, 10 ° C / min, and load 49 mN in the first cycle, and -100 to 330 ° C, 10 ° C / min, and load 49 mN in the second cycle. The intersection of the tangent of the expansion curve from room temperature to the glass transition point in the second cycle and the tangent after the glass transition point was taken as the glass transition temperature. The results are shown in Table 1.

[0147] <Viscosity measurement> Using a BF type viscometer (device name: DV3T, manufactured by Brookfield), the viscosity of the conductive paste immediately after preparation was measured at the following measurement temperature and rotation speed. The results are shown in Table 1. η0.5: Rotation speed 0.5 rpm, shear rate 1.92 s -1 , measurement temperature 25℃ η5: Rotation speed 5 rpm, shear rate 19.2 s -1 , measurement temperature 25℃ The thixotropy index (η0.5 / η5) was also calculated, and the results are shown in Table 1.

[0148] <Adhesion strength measurement> The conductive paste obtained by the above method was applied onto a silver lead frame, and then a silver-plated silicon chip measuring 2.0 mm long x 2.0 mm wide x 350±5 μm thick was placed on the conductive paste. The temperature was raised from 25°C to 175°C over 30 minutes, and then heat-treated at 175°C for 1 hour to obtain a cured sample. The die shear strength of the silver lead frame and silicon chip at 260°C and a shear speed of 500 μm / sec was measured using a Dage4000 (manufactured by Nordson Advanced Technologies). The results are shown in Table 1.

[0149] <Dynamic storage modulus measurement> The conductive paste obtained by the above method was applied in a strip shape with a width of 4 mm × a length of 20 mm × a thickness of 300 μm on a Teflon (registered trademark) plate, heated from 25°C to 175°C at a heating rate of 5°C / min, and then continuously heated at 175°C for 1 hour to obtain a cured sample. The obtained cured sample was peeled off from the Teflon (registered trademark) plate, and the dynamic storage modulus was measured using SII DMS6100 (manufactured by Hitachi High-Technologies Corporation) under the conditions of 25°C (or 250°C), tensile mode, and a frequency of 10 Hz. The results are shown in Table 1.

[0150] <CTE Measurement> The conductive paste obtained by the above method was applied in a strip shape with a width of 4 mm × a length of 10 mm × a thickness of 150 μm on a Teflon (registered trademark) plate, heated from 25°C to 175°C at a heating rate of 5°C / min, and then continuously heated at 175°C for 5 hours to obtain a cured sample. The obtained cured sample was peeled off from the Teflon (registered trademark) plate, and TMA (thermomechanical analysis) was measured using a TMA apparatus (SII SS7100, manufactured by Hitachi High-Technologies Corporation) under the conditions of 30 to 200°C, 10°C / min, a load of 49 mN for the first cycle, and -100 to 330°C, 10°C / min, a load of 49 mN for the second cycle. Then, the average linear expansion coefficient (CTEα1) was calculated from the slope of the tangent line of the expansion curve from the measurement start temperature of the second cycle to the glass transition point, and the average linear expansion coefficient (CTEα2) was calculated from the slope of the tangent line of the expansion curve after the glass transition point of the second cycle. The results are shown in Table 1.

[0151] <Volume Resistivity Measurement> The conductive paste obtained by the above method was applied in a strip shape with a width of 4 mm × a length of 40 mm × a thickness of 0.05 mm on a glass plate. Then, the coated layer of the conductive paste was heated from 25°C to 175°C at a heating rate of 5°C / min in a nitrogen atmosphere with a residual oxygen concentration of less than 1000 ppm, and then heat-treated under the conditions of 175°C and 60 minutes to form a cured layer of the conductive paste. The resistance value of the obtained cured layer of the conductive paste was measured using a milliohm meter (manufactured by HIOKI) with electrodes having an electrode interval of 40 mm by the DC four-electrode method, and the volume resistivity was calculated. The unit is Ω·cm. The results are shown in Table 1.

[0152] [Table 1] [Explanation of symbols]

[0153] 100 Semiconductor device 10 Adhesive layer 20 Semiconductor elements 30 Base material 32 Die pad 34 Outer lead 40 Bonding Wire 50 Sealing resin< / cte>

Claims

1. A conductive paste comprising a thermosetting resin (A), silver particles (b1), and alumina particles (b2), the content of the silver particles (b1) is 20% by mass or more and 65% by mass or less, when the total amount of the conductive paste is 100% by mass, The conductive paste has a viscosity of 0.1 Pa·s or more and 150 Pa·s or less, as measured using a BF type viscometer at a temperature of 25° C. and a rotation speed of 5 rpm.

2. 2. The conductive paste according to claim 1, wherein a total content of the silver particles (b1) and the alumina particles (b2) is 40 mass% or more and 99 mass% or less when a total amount of the conductive paste is 100 mass%.

3. 3. The conductive paste according to claim 1, wherein the content of the thermosetting resin (A) is 1 mass % or more and 30 mass % or less when the total amount of the conductive paste is 100 mass %.

4. The conductive paste according to claim 1 or 2, wherein the thermosetting resin (A) comprises one or more resins selected from the group consisting of an epoxy resin (a1) and a (meth)acrylic resin (a2).

5. The thermosetting resin (A) contains the epoxy resin (a1), The conductive paste of claim 4 , further comprising a (meth)acrylate compound.

6. The thermosetting resin (A) contains the (meth)acrylic resin (a2), The conductive paste of claim 4 , wherein the conductive paste further comprises a (meth)acrylate compound and a low stress agent.

7. The silver particles (b1) have an average particle size D based on a volume-based particle size distribution measured by a flow particle image analyzer. 50 The flake silver particles have different The conductive paste according to claim 1 or 2, wherein the alumina particles (b2) include spherical particles.

8. The flake silver particles have an average particle size D 50 flake-shaped silver particles having an average particle diameter D of 0.1 μm or more and less than 6 μm; 50 and flake-shaped silver particles having a size of 6 μm or more and 20 μm or less.

9. The average particle size D of the silver particles (b1) based on a volume-based particle size distribution measured using a flow particle image analyzer 50 (d1) and the average particle diameter D of the alumina particles (b2) 50 The conductive paste according to claim 7 , wherein the ratio (d1 / d2) to (d2) is 1 or more and 4 or less.

10. 3. The conductive paste according to claim 1, wherein the viscosity of the conductive paste measured using a BF type viscometer at a temperature of 25° C. and a rotation speed of 0.5 rpm is η0.5, and the viscosity of the conductive paste measured at a temperature of 25° C. and a rotation speed of 5 rpm is η5. The conductive paste according to claim 1, wherein the thixotropic index, which is a viscosity ratio (η0.5 / η5), is 0.1 or more and 20 or less.

11. The volume resistivity measured by the following method is 9.0×10 -2 The conductive paste according to claim 1 or 2, having a resistivity of Ω·cm or less. (method) The conductive paste is applied onto a glass plate in a strip shape of 4 mm wide x 40 mm long x 0.05 mm thick. The conductive paste coating layer is then heated from 25°C to 175°C at a heating rate of 5°C / min in a nitrogen atmosphere with a residual oxygen concentration of less than 1000 ppm, and then heat-treated at 175°C for 60 minutes to form a hardened layer of the conductive paste. The resistance of the hardened layer of the conductive paste obtained is measured by a direct current four-electrode method using electrodes with an electrode spacing of 40 mm, and the volume resistivity is calculated.

12. A highly thermally conductive material comprising a cured product of the conductive paste according to claim 1 or 2.

13. A substrate; A semiconductor element mounted on the base material via an adhesive layer, The semiconductor device, wherein the adhesive layer comprises a cured product of the conductive paste according to claim 1 .

Citation Information

Patent Citations

  • Thermosetting resin composition, semiconductor device and electric / electronic component

    JP2014194013A